Educational Qality Improvement Strategy State MTs Students In Banyumas - Muflihin, Muh. Hizbul (The International Journal of Education Management and Sociology, 2023)
The aims of this research are: To find out the strategy for improving the quality of education at MTs Negeri 1 in Banyumas. To find out the factors that support and hinder the improvement of the quality of education. To find out the efforts to overcome obstacles in improving the quality. The research method uses a qualitative approach that describes the phenomena that occur in the Madrasah Tsanawiyah Negeri 1 environment. Data collection techniques are through interviews with teachers and vice principals in curriculum areas and third grade students. The conclusion in improving the quality of MTs Negeri 1 Banyumas is the most basic on two main things, namely the academic and non-academic fields. Factors supporting learning, such as facilities that are quite complete, but still need to be improved in quantity and quality. Efforts made by the head of Madrasah MTs Negeri 1, in improving the quality of education to be able to realize an active, creative, effective and fun learning process, as well as carry out evaluations for continuous improvement. Implications in improving the quality of madrasas, it is necessary to get attention from various parties so that it has an impact on the management of the quality of education. By fulfilling learning facilities, budget allocation can improve the discipline of madrasah management. With a focus on research strategies to improve the quality of MTs Negeri 1, it will have an impact on future researchers to be more in-depth in research, especially in terms of research variables